2020
DOI: 10.1088/1755-1315/599/1/012024
|View full text |Cite
|
Sign up to set email alerts
|

Review design of E-Motorcycle charger topology for DC house using planar magnetics

Abstract: Following the global trend of adopting renewable energy into the electric power system, many direct currents (DC) houses concepts are proposed. Most of the renewable energy systems are based on DC voltage sources. This paper discussed the development of a lightweight, low-profile, and built-in electric motorcycle (E-Motorcycle) charger that does not take excessive space and compatible with the DC house system. A topology comparison in high switching frequency above 1 MHz using planar magnetics is performed to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…This study identified a number of elements and obstacles in the development of EV charging control in nextgeneration smart grid applications, as well as possible solutions. Although having a sufficient number of charging stations to meet demand is important in encouraging the use and adoption of EMCs, the effect of EMC charging on the electrical infrastructure must be taken into account to prevent the dangers of electrical and electromagnetic interference [15][16][17][18][19][20][21]. Yuwei Jin [17] conducted a sensitivity analysis of active power and voltage to identify the impact of EV charging on different load profiles.…”
Section: Introductionmentioning
confidence: 99%
“…This study identified a number of elements and obstacles in the development of EV charging control in nextgeneration smart grid applications, as well as possible solutions. Although having a sufficient number of charging stations to meet demand is important in encouraging the use and adoption of EMCs, the effect of EMC charging on the electrical infrastructure must be taken into account to prevent the dangers of electrical and electromagnetic interference [15][16][17][18][19][20][21]. Yuwei Jin [17] conducted a sensitivity analysis of active power and voltage to identify the impact of EV charging on different load profiles.…”
Section: Introductionmentioning
confidence: 99%